Employee Motivation and its Impact on Organizational Performance - Sifa Malinda; Nurul Hidayatul Jannah; Lailatul Badriyah; Muhammad Riski; Mada Aditia Wardhana (Jurnal Manajemen Bisnis Era Digital, 2025)
In today’s rapidly changing global context, employee motivation has emerged as a strategic issue in human resource management, particularly in sustaining organizational productivity and competitiveness. Developments such as digitalization, economic uncertainty, and workplace transformation have prompted companies to focus more deeply on effective motivational approaches. Recognizing the role of motivation in influencing employee retention, productivity, and operational efficiency, this study conducts a Systematic Literature Review (SLR) to map key concepts and empirical trends regarding the relationship between employee motivation and organizational performance. Grounded in theoretical frameworks such as Maslow’s Hierarchy of Needs, Herzberg’s Two-Factor Theory, and Self-Determination Theory, the study examines major drivers including leadership, compensation, and work-life balance. Findings reveal paradoxes in motivational strategy effectiveness across sectors and highlight research gaps, particularly in cross-industry approaches and integrative synthesis. This study provides valuable contributions for academics and practitioners in designing evidence-based, context-relevant motivation strategies aligned with the dynamics of modern organizations.